Pengaruh Kepatuhan Pelaporan Keuangan, Kompetensi Aparatur Desa, Sistem Pengendalian Internal dan Whistleblowing System terhadap Pencegahan Fraud Dana Desa - Putri, Ni Ketut Ayu Riani; Kisnawati, Baiq (Sekolah Tinggi Ilmu Ekonomi AMM, 2024)
This research aims to determine the influence of financial reporting compliance, village apparatus competency, internal control system and whistleblowing system on fraud prevention in managing village funds in Gerung District. This research uses quantitative methods with an associative approach, the data source in this research uses primary data obtained through distributing questionnaires. This research variable consists of 4 (four) independent variables, namely financial reporting compliance, village apparatus competency, internal control system and whistleblowing system with the dependent variable namely fraud prevention in managing village funds. The population in this research is all village officials in Gerung District, West Lombok Regency. Samples were taken using saturated samples or using the entire population as the research sample, namely 93 village officials. The analytical method used in this research is the multiple linear regression analysis method. The test results show that financial reporting compliance and the internal control system do not have a significant effect on fraud prevention in village fund management in Gerung District, West Lombok Regency. Meanwhile, the competence of village officials and the whistleblowing system have a positive and significant effect on preventing fraud in managing village funds in Gerung District, West Lombok Regency. The results of this research also show that the independent variable is able to influence the dependent variable by 36.7% while the remaining 63.3% is explained by other causes that are not included in this research.